Multi-stage treatment of esophago-tracheal injury after button battery ingestion - Piotr Skrzypczak; Piotr Nogal; Patrycja Sosnowska; Jarosław Szydłowski; Przemysław Mańkowski (Elsevier, 2020)
The aspiration of the foreign body is a common problem in any pediatric specialization. We present a case of a 3-year-old boy admitted to the hospital after the button battery ingestion. In diagnostic imaging, a bronchoesophageal fistula was found. Gastrostomy and ileostomy were obtained. Due to increasing respiratory failure, the tracheotomy was made and the patient was intubated with the bilateral bronchopulmonary tube. On the 25th day, an attempt to reconstruct the esophagus and trachea was taken. During the operation, the surgery team took the cartilage lobe of the left ear, then switched to the extracorporeal circulation and finally made the esophagus end to end anastomosis and reconstruction of the tracheal loss with cartilage.On the 45th day, the communication between the esophagus and the trachea was found. A esophagostomy was made, and salivary glands were injected with botulinum toxin. The tightness of the anastomosis was confirmed. The patient in the favorable general condition left the ward on the 103rd day of stay. In cases of the trachea, bronchus, or esophagus damages, the prognosis is very serious. The therapeutic success depends on the cooperation of many specialists, both the non-surgical and operational specializations.